Formulation and Evaluation of Antifungal Nanocream for Topical Drug Delivery - Payal Mahendra Jadhav; Dr. Ajay Randhir Fugate; Dr. Vishweshwar Mahishankar Dharashive; Vaishnavi Laxmikant Havale (Asian Journal of Pharmaceutical Research and Development, 2025)
The objective of this study was to develop and optimize a nanostructured lipid carrier (NLC)-based nano cream loaded with Voriconazole for enhanced topical antifungal delivery. Voriconazole, a hydrophobic antifungal agent, exhibits poor aqueous solubility and variable bioavailability, making it a suitable candidate for lipid-based nano systems. Preformulation studies confirmed the drug's purity and solubility profile. Voriconazole was identified as a whitecrystallinepowderwithameltingpointof128–130°Canddemonstratedgoodsolubility in methanol, ethanol, and DMSO. FTIR analysis confirmed the absence of significant drug– excipient interactions. NLCs were prepared via hot homogenization followed by ultrasonication, employing glyceryl monostearate and oleic acid as solid and liquid lipids, respectively, with Tween 80 and Poloxamer 188 as surfactants. A 3² factorial design was utilized to optimize formulations based on particle size and entrapment efficiency .Among the nine experimental batches, Batch F6 exhibited optimal characteristics,with a particle size of 182nm,PD Iof 0.22, zeta potential of –30 mV, entrapment efficiency of 89.41%, and drug loading of 31.8%. Batch F6 was further incorporated into four nano cream formulations (F1–F4), varying in Carbopol 940 and stearic acid concentrations. Formulation F3 was identified as optimal, demonstrating excellent spreadability (6.1 gm.cm/sec), drug content (100.5%), and sustained drug release (79.5%over8hours). Anti fungal activity one of inhibition was found as 38mm. The optimized cream also maintained its physical stability, pH, and drug content under accelerated stability testing. In conclusion, the developed Voriconazole-loaded NLC-based nano cream presents a promising and patient-compliant approach for effective topical antifungal therapy, offering improved drug delivery, stability, and therapeutic efficacy.